2020
DOI: 10.1074/jbc.rev120.015101
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing, quantifying, and manipulating mitochondrial DNA in vivo

Abstract: Mitochondrial DNA (mtDNA) encodes proteins and RNAs that support the functions of mitochondria and thereby numerous physiological processes. Mutations of mtDNA can cause mitochondrial diseases and are implicated in ageing. The mtDNA within cells is organized into nucleoids within the mitochondrial matrix, but how mtDNA nucleoids are formed and regulated within cells remains incompletely resolved. Visualization of mtDNA within cells is a powerful means by which mechanistic insight can be gained. Manipulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 155 publications
(261 reference statements)
0
21
1
Order By: Relevance
“…Additionally, restriction enzymes, such as EcoRI, PstI, or XhoI, can be targeted to mitochondria used to decrease or eliminate mtDNA in cells. Manipulation of the mtDNA copy number can also be achieved by alteration of the mtDNA replication machinery ( Bacman et al, 2014 ; Prole et al, 2020 ). Overexpression or knockdown of the key component TFAM will increase or decrease the mtDNA number ( Lewis et al, 2016 ; Desdin-Mico et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, restriction enzymes, such as EcoRI, PstI, or XhoI, can be targeted to mitochondria used to decrease or eliminate mtDNA in cells. Manipulation of the mtDNA copy number can also be achieved by alteration of the mtDNA replication machinery ( Bacman et al, 2014 ; Prole et al, 2020 ). Overexpression or knockdown of the key component TFAM will increase or decrease the mtDNA number ( Lewis et al, 2016 ; Desdin-Mico et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nucleoside analogs, such as the antiretroviral drug zalcitabine that inhibit mitochondrial POLG and cause a decrease in mtDNA copy number, have been used to manipulate mtDNA counts in cells ( Young and Copeland, 2016 ). Moreover, it is predicted that alterations in mitochondrial network fragmentation, which is intimately involved in mechanisms of mitophagy, including Drp1, Opa1, and Mfn1/2, may also enhance the breakdown of mtDNA ( Giacomello et al, 2020 ; Prole et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This question in particular is of broad interest as several studies have reported that cationic dyes could target secondary DNA structures in mtDNA but without providing direct evidence [20] . Furthermore finding new labels with a variety of excitation wavelengths for visualizing mtDNA is also of great interest as mentioned in a recent report [21] . Therefore, stimulated by the recent impetus for dye targeting mitochondria, it was decided to address these questions through molecular engineering of the TP‐2Bzim compound (Figure 1), which represents the best candidate of the TPA series in terms of brightness and DNA binding affinity.…”
Section: Introductionmentioning
confidence: 99%